Characteristics of cause of death and triggers for crisis in patients with myasthenia gravis. Issue 3 (8th March 2022) - Sugimoto, Takamichi; Ochi, Kazuhide; Yamawaki, Takemori; Naito, Hiroyuki; Ohno, Narumi; Nomura, Eiichi; Kohriyama, Tatsuo; Maruyama, Hirofumi
Abstract: Introduction: Improving our knowledge on the cause of death and triggers of crisis in myasthenia gravis (MG) patients may have a patient be careful in the daily life. Methods: We selected 233 MG patients with regular visits to our hospital between 1st May 2006 and 31 December 2018. We investigated the cause of death and trigger of crisis at our hospital. Results: Eight MG patients were confirmed to die during the observation period, and the causes of death were four cases of cancer (breast cancer, pancreatic cancer, stomach cancer, and cancer of an unknown primary site) and two cases of sudden death (sudden cardiac arrest and cardiac arrest from choking), invasive thymoma, and vertebral artery dissection. Fourteen patients experienced crisis, and the most common trigger of crisis was respiratory infection, followed by cholinergic and intravenous methylprednisolone. Conclusion: The most common cause of death was cancer, and the most common trigger of crisis was respiratory infection. Sudden death was characteristic of MG patients. Respiratory infection and malignancy should be considered in MG patients regularly to prevent crisis and death. Further research on sudden death in MG patients should be performed.